Cross-boundary marketing: sensitivity to global convergence or global individualism? - Moutinho, Luiz (Henry Stewart Talks, 2009)
International trade, Trends: globalization, market integration, labour markets and social change, What Europe looks like, Emerging economies coming out ahead, The end of the multinational business model?, Local sensitivity, Global individualism, Bottom-up approach, 'Coopetition' gaining acceptance, Managing in a borderless world, Collaborative marketing and commerce, International sourcing and procurement